Accountability Practices in Performance-Based Education Planning: A Case Study of Sabilal Muhtadin Islamic High School, Banjarmasin - Azizah, Wafa Nur; Lyana, Sisca; Suhaimi,; Sulistiyana, (Jurnal Paedagogy, 2026)
This study aims to analyze the implementation of performance-based educational planning accountability and its role in strengthening school governance at SMA Islam Sabilal Muhtadin Banjarmasin. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and document analysis involving the school principal, teachers, school management team, and school committee members. Informants were selected purposively based on their direct involvement in school planning and evaluation processes, while data credibility was ensured through source and method triangulation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results showed that performance-based educational planning accountability in schools is implemented through four main mechanisms: strategic planning based on performance indicators, integration of program planning with school budgeting, data-driven monitoring and evaluation, and transparent reporting to stakeholders. This study highlights the importance of strengthening organizational capacity and promoting data-driven decision-making to enhance the effectiveness of accountability practices in school management.